Pheromone peptide cOB1 from native Enterococcus faecalis forms amyloid‐like structures: A new paradigm for peptide pheromones. (17th July 2019) - Gour, Shalini; Kumar, Vijay; Rana, Monika; Yadav, Jay Kant
Abstract : Pheromone peptides are an important component of bacterial quorum‐sensing system. The pheromone peptide cOB1 (VAVLVLGA) of native commensal Enterococcus faecalis has also been identified as an antimicrobial peptide (AMP) and reported to kill the prototype clinical isolate strain of E. faecalis V583. In this study, the pheromone peptide cOB1 has shown to form amyloid‐like structures, a characteristic which is never reported for a pheromone peptide so far. With in silico analysis, the peptide was predicted to be highly amyloidogenic. Further, under experimental conditions, cOB1 formed aggregates displaying characteristics of amyloid structures such as bathochromic shift in Congo red absorbance, enhancement in thioflavin T fluorescence, and fibrillar morphology under transmission electron microscopy. This novel property of pheromone peptide cOB1 may have some direct effects on the binding of the pheromone to the receptor cells and subsequent conjugative transfer, making this observation more important for the therapeutics, dealing with the generation of virulent and multidrug‐resistant pathogenic strains. Abstract : cOB1, being a sex pheromone, is a part of conjugative gene transfer. The binding of pheromone to the specific receptor of donor cell ultimately leads to the transfer of mobile genetic elements and generation of virulent strains (A). We propose that after the aggregation (B), cOB1 amyloids may not bind effectively to the pheromone receptor, resulting in the blockage of the above mentioned gene transfer, thus could work as a preventive mechanism against propagation of bacterial virulence.